Discourses that matter: wole soyinka’s theatre as a form of representing and reading the world - Figueiredo, Rosa Branca (2016)
Wole Soyinka is a most significant figure in contemporary world literature. From the perspectives of the politics of postcolonial writings, perhaps the ultimate challenge of the complexity of Soyinka’s works and career lies in the fact that the metanarratives that imaginatively and discursively underwrote the great liberation movements of the twentieth century do not feature in his works in their conventional and familiar configurations. Overarching all the struggles waged by these movements is the struggle for self-representation as the existential and expressive roots of human freedom.The best examples of this structure in Soyinka’s theatre are A Dance of the Forests, Kongi’s Harvest, Madmen and Specialists and From Zia With Love. Soyinka’s critical essays also operate in a great variety of social and intellectual contexts and cover an extraordinary range of topics, including literary criticism and aesthetic theory, theatre and cultural history, political power and ideology, and, more recently religious extremism and nuclear pollution. One “form of attention” which has been influential in the reception of Soyinka’s works is that of professional critics, especially with regard to the institutionalisation of the academic study of Anglophone writings of the developing world in the second half of the twentieth century.